2013
DOI: 10.5861/ijrset.2013.434
|View full text |Cite
|
Sign up to set email alerts
|

A study on the relationship of Facebook and EFL learners’ personality

Abstract: Social networking software or what people are more familiar with "Facebook" has truly affected each and every person in the world. More so with students, Facebook has already become part of their daily activities. In an English as a Foreign Language (EFL) setting, it is quite interesting if students would also spend the same time and effort in learning a foreign language. With this in mind, the current study describes the various background factors regarding students' use of Facebook in a science and technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…In their own study, they reported an average of 47 minutes of online time for FB users every day. Wang and Ching (2013), on the other hand, identified that 46% of the students interviewed admitted they tend to use their Facebook account at least once or twice a day for an average of 3 minutes only per day. The usage is lower compared with the findings of previous studies.…”
Section: Time Spent Using Facebookmentioning
confidence: 98%
“…In their own study, they reported an average of 47 minutes of online time for FB users every day. Wang and Ching (2013), on the other hand, identified that 46% of the students interviewed admitted they tend to use their Facebook account at least once or twice a day for an average of 3 minutes only per day. The usage is lower compared with the findings of previous studies.…”
Section: Time Spent Using Facebookmentioning
confidence: 98%
“…მე ტიც, რო გორც ერ თ-ერ თი კვლე ვა აჩ ვე ნებს, მა თი თვით პრე ზენ ტა ცია სტრა ტე გი უ ლია . ზო გა დად, ნევ რო ტიზ მი სა და სო ცი ა ლუ რი ქსე ლე ბის გა მო ყე ნე ბის ურ თი ერ თმი მარ თე ბის შე სა ხებ მო ნა ცე მე ბი არა ერ თგვა რო ვა ნი ა. კერ ძოდ, ზო გი კვლე ვა ზო მი ერ და დე ბით (Giota & Kleftaras, 2013;Wang & Ching, 2013) კავ შირ ზე მი უ თი თებს, ზო გი -სუსტ და დე ბით (Huang, 2019;, ან და სუ ლაც ნუ ლო ვან კო რე ლა ცი ა ზე . მა შინ, რო ცა სხვა კვლე ვე ბი ნევ რო ტიზ მსა და სო ცი ა ლუ რი ქსე ლე ბის მოხ მა რე ბას შო რის უარ ყო ფით კავ შირს აჩ ვე ნე ბენ Lee et al, 2011;Marino et al, 2016;.…”
Section: ფე ის ბუ ქის გა მო ყე ნე ბის მო ტი ვე ბიunclassified